Qualitative Evaluation of Actors of Regional Development on the Example of a Regional Labour Market - Hlavaćek, Petr (Ocena jakościowa czynników rozwoju regionalnego na przykładzie regionalnego rynku pracy, 2008)
Evaluation of actors is influenced by their level of concentration that could result in -increasing level of concentration means also higher agglomeration and location savings of a region, quicker transfer of codified and non-codified knowledge has positive influence on actors' flexibility and dynamics of regional atmosphere development. An added value is formed by direct and indirect regional advantages! qualitative changes of social and cultural atmosphere of a region. If there is a potential for networking among actors, the key subjects of regional development have the role of initiators of establishing these nets on the basis of sector and intersector links. In connection with new programming term structural funds represent great impulse also for initiation and development of networking as an important SOE location factor. Development of regional economics and social atmosphere is therefore in close connection to the sources of public support that should be the source of institutional changes in regions as well.(excerpt from the article)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 257-267